2019
DOI: 10.7554/elife.39656
|View full text |Cite
|
Sign up to set email alerts
|

Time preferences are reliable across time-horizons and verbal versus experiential tasks

Abstract: Individual differences in delay-discounting correlate with important real world outcomes, for example education, income, drug use, and criminality. As such, delay-discounting has been extensively studied by economists, psychologists and neuroscientists to reveal its behavioral and biological mechanisms in both human and non-human animal models. However, two major methodological differences hinder comparing results across species. Human studies present long time-horizon options verbally, whereas animal studies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 98 publications
(136 reference statements)
3
16
1
Order By: Relevance
“…The lack of correlation between tasks observed here is in line with the results of Johnson [ 38 ], who similarly found that decisions across an experiential task (using coins immediately available) and a hypothetical task (using hypothetical amounts of money) were not significantly correlated. The results, however, contrast with those of Lukinova and colleagues [ 37 ] whose experiential task used rewards that could be experienced less directly (depiction of money on a computer screen). Taken together, these results may point to the consumability of rewards as an important feature of experiential tasks; that is, it may be critical that rewards are available to direct experience if they are to inform the value of subsequent choices.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The lack of correlation between tasks observed here is in line with the results of Johnson [ 38 ], who similarly found that decisions across an experiential task (using coins immediately available) and a hypothetical task (using hypothetical amounts of money) were not significantly correlated. The results, however, contrast with those of Lukinova and colleagues [ 37 ] whose experiential task used rewards that could be experienced less directly (depiction of money on a computer screen). Taken together, these results may point to the consumability of rewards as an important feature of experiential tasks; that is, it may be critical that rewards are available to direct experience if they are to inform the value of subsequent choices.…”
Section: Discussioncontrasting
confidence: 99%
“…Because of experimental constraints, the experiential and hypothetical intertemporal choice tasks necessarily differed not only in the experience of delays and rewards, but also in the time scale of the delays (seconds versus days to years), the costs incurred by the delays, and the nature of the rewards. Differences in time scale are unlikely to explain our findings, as evidence suggests that subjective value brain signals during intertemporal choice tasks adapt to the range of values employed in the experimental context [ 35 ], and correlations across tasks with distinct temporal scales have been reported with monetary rewards [ 37 ]. Differences in costs associated with the delay have been highlighted as a key confound in comparisons between experiential and hypothetical intertemporal choice tasks [ 122 ] and were also present in the current study: the experiential task required waiting for the reward without distraction (high delay cost), whereas the hypothetical task did not specify the conditions of the hypothetical delay, and therefore participants could presumably resume normal daily life during that period of time (low to no delay cost).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis that people rather focus on numbers than the accompanying units is corroborated by findings that cooperation level of participants in the prisoner’s dilemma game increased when the reward was increased from 3ȼ to 300ȼ, but not when it was increased from 3ȼ to 3$ (Furlong and Opfer, 2009). However, presentation format does not always alter time-preferences (Lukinova et al, 2019). In an intertemporal decision making study, time-intervals were indicated textually (ex.…”
Section: Discussionmentioning
confidence: 99%